2021
DOI: 10.1073/pnas.2017779118
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Hedgehog signal transduction in adult astrocytes results in region-specific blood–brain barrier defects

Abstract: Significance Several signaling pathways have been implicated in regulating blood–brain/spinal cord barrier (BBB) properties in the adult mammalian central nervous system (CNS). However, it has become clear that the role of the Sonic hedgehog pathway has not been accurately defined. The current work addresses this issue by demonstrating that the pathway is required in protoplasmic astrocytes to maintain specific BBB characteristics in select regions of the CNS. In contrast to prior studies, we find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Immuno-histochemistry and immunofluorescence analyses of β-gal + cells, in combination with different glial makers, showed that most of the Hh-responding cells (β-gal + cells) in the spinal cords of the ptch +/− mice induced to EAE were astrocytes ( Figure 8 B) located in the grey matter ( Figure 8 A) regardless of disease stage. This is in agreement with previous reports showing that astrocytes are the predominant Hh-responding cells in the nervous system [ 38 ]. Similar to Ligon et al [ 39 ], we also show that a high percentage of nuclei positive for β-gal + nuclei localise in NG2 + OPCs, which in turn express Olig1 and Olig 2 markers ( Supplementary Figures S2 and S3 ).…”
Section: Discussionsupporting
confidence: 94%
“…Immuno-histochemistry and immunofluorescence analyses of β-gal + cells, in combination with different glial makers, showed that most of the Hh-responding cells (β-gal + cells) in the spinal cords of the ptch +/− mice induced to EAE were astrocytes ( Figure 8 B) located in the grey matter ( Figure 8 A) regardless of disease stage. This is in agreement with previous reports showing that astrocytes are the predominant Hh-responding cells in the nervous system [ 38 ]. Similar to Ligon et al [ 39 ], we also show that a high percentage of nuclei positive for β-gal + nuclei localise in NG2 + OPCs, which in turn express Olig1 and Olig 2 markers ( Supplementary Figures S2 and S3 ).…”
Section: Discussionsupporting
confidence: 94%
“…The role of astrocyte-derived Shh was proposed in maintaining the BBB via a mechanism involving regulation of TJ protein expression by BVMECs [ 37 ]. Nevertheless, transcriptomic studies have begun to point out that post-mitotic astrocytes, and not BMECs, represent the primary responders to hedgehog signalling in the adult brain [ 63 ]. Astrocytes are also involved in strengthening the TJ, whose maturation is promoted by release of glial cell-derived neurotrophic factor (GDNF), an EC ligand for the GDNF family receptor alpha-1 (GFRA-1).…”
Section: Components Of the Blood–brain Barrier (Bbb)mentioning
confidence: 99%
“…In contrast, astrocytes, which were historically believed to be essential to BBB development and maintenance 6 , now have a less clear role in these activities. Seminal transplantation experiments in non-neural tissues showed that astrocytes could induce barrier properties in non-BBB endothelial cells 7,8 , and subsequent studies have shown that astrocyte-secreted factors such as sonic hedgehog and angiotensin can support BBB function [9][10][11] . Similarly, primary endothelial cells purified by immunopanning methods induced astrocyte precursor cells to differentiate into astrocytes via leukemia inhibitory factor (LIF) or LIF-like cytokines 12 , suggesting a close temporal and spatial correlation between endothelial and astrocyte differentiation.…”
mentioning
confidence: 99%